Investigation of the Finishing Technology of SLM Implants - Ablyaz Timur; Muratov Karim; Shlykov Evgenii; Osinnikov Ilia; Konogorova Luiza (MATEC Web of Conferences, 2021)
In this research, the use of plasma electrolytic polishing (PEP) as a finishing treatment of materials obtained by the SLM method from CoCr30 cobalt-chromium powder is proposed. To assess the possibility of using this method, a simulator sample was used. The imitation sample was polished for 60 seconds. The roughness and the size of the removal material were measured. Based on the results obtained for the simulator sample, a conclusion was made about the possibility of using PEP technology for finishing the treatment stent. The stent simulator was also polished. The processing time was 30s and 60s. The geometric parameters were measured, and the removal material was calculated. Images of the stent surface were taken before and after PEP. It was found that with an increase in the processing time from 30 to 60 seconds, the allowance removed from all surfaces increases almost twice. The possibility of using the PEP technology as a finishing operation for the manufacture of stents from cobalt-chromium alloys is shown.